Family and Academic Stress and Their Impact on Students' Depression Level and Academic Performance - Deng, Yuwei; Cherian, Jacob; Khan, Noor Un Nisa; Kumari, Kalpina; Sial, Muhammad Safdar; Comite, Ubaldo; Gavurova, Beata; Popp, József (Frontiers in Psychiatry, 2022)
Current research examines the impact of academic and familial stress on students' depression levels and the subsequent impact on their academic performance based on Lazarus' cognitive appraisal theory of stress. The non-probability convenience sampling technique has been used to collect data from undergraduate and postgraduate students using a modified questionnaire with a five-point Likert scale. This study used the SEM method to examine the link between stress, depression, and academic performance. It was confirmed that academic and family stress leads to depression among students, negatively affecting their academic performance and learning outcomes. This research provides valuable information to parents, educators, and other stakeholders concerned about their children's’ education and performance.